2019
DOI: 10.1021/acssuschemeng.9b02585
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric Evaluation of the Operational Thermal Stability of Ribonuclease A in Hydrated Deep Eutectic Solvents

Abstract: Deep eutectic solvents (DESs), and particularly their mixtures with water, have been postulated as progressive, sustainable biocatalytic media. Currently, however, knowledge of biomolecular stability within DES media, such as protein folding reversibility, remains quite limited. In this Letter, we present the findings of a study of bovine ribonuclease A (RNase A) unfolding/refolding within aqueous media containing 5–35 wt % of illustrative DESs comprising 1:2 molar ratios of choline chloride plus urea (so-call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…These results indicate that the specific concentration of ChCl -Lac may be able to provide a suitable microenvironment by hydrogen bonding in the active center of enzyme, and then keep its rigid confirmation and function especially at a high temperature. This result is in agreement with other’s observation and conclusion that the DES could promote the thermal stability of enzymes ( Kist et al, 2019 ). Interestingly, DESs not only can stabilize the enzyme at high temperature, but some of them also have been reported to increase the laccase stability at low temperature.…”
Section: Results and Analysissupporting
confidence: 94%
“…These results indicate that the specific concentration of ChCl -Lac may be able to provide a suitable microenvironment by hydrogen bonding in the active center of enzyme, and then keep its rigid confirmation and function especially at a high temperature. This result is in agreement with other’s observation and conclusion that the DES could promote the thermal stability of enzymes ( Kist et al, 2019 ). Interestingly, DESs not only can stabilize the enzyme at high temperature, but some of them also have been reported to increase the laccase stability at low temperature.…”
Section: Results and Analysissupporting
confidence: 94%
“…Kist et al demonstrated that a single DSC thermal cycle to 80 °C in water containing 10 wt % or more reline results in the rapid and total loss of folding reversibility for bovine ribonuclease A (RNase A), an outcome partly attributed to ammonia evolution. For this reason, use of 1,3-dimethylurea in place of urea led to slightly better outcomes . In stark contrast, the inclusion of glyceline up to at least 35 wt % in aqueous media increased the T m and improved the thermodynamic stability of RNase A beyond the natural water environment.…”
Section: Selected Applications Of Deep Eutectic Solventsmentioning
confidence: 99%
“…For this reason, use of 1,3-dimethylurea in place of urea led to slightly better outcomes. 185 In stark contrast, the inclusion of glyceline up to at least 35 wt % in aqueous media increased the T m and improved the thermodynamic stability of RNase A beyond the natural water environment. Indeed, iterative thermal cycling resulted in only minor losses in the experimental heat capacity, reflecting a small degree of irreversibly unfolded RNase A in glyceline-containing systems.…”
Section: Biomolecular Structure Folding and Stabilitymentioning
confidence: 99%
“…25 In addition to this, DESs are also suitable for protein extraction providing enhanced yield. 18,26 Kist et al 27 have presented work on thermodynamic refolding of RNase by using hydrated cholinium chloride-based DESs. Thus, DESs are currently attracting noteworthy recognition as "greener" media for a variety of biological as well as biochemical processes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was found that B-form helical structures of DNA were well preserved in DESs along with exhibiting enhanced thermal and pH stability of regenerated DNA. , Zhao further deduced that G-quadruplexes of DNA were more stable in neat DESs compared to aqueous media, even at temperatures greater than 110 °C . In addition to this, DESs are also suitable for protein extraction providing enhanced yield. , Kist et al have presented work on thermodynamic refolding of RNase by using hydrated cholinium chloride-based DESs. Thus, DESs are currently attracting noteworthy recognition as “greener” media for a variety of biological as well as biochemical processes.…”
Section: Introductionmentioning
confidence: 99%